Fast Polymerization of Dopamine for Coating on ANPZO Surface with Excellent Thermal Stability and Mechanical Properties. Issue 5 (3rd March 2022) - Jia, Kanghui; Liu, Yucun; Chai, Tao; Yu, Yanwu; Jing, Suming; Wu, Pengfei; He, Jinxuan; Zhang, Wei
Abstract: Mussel‐inspired dopamine has been employed extensively in the field of surface modification, and polydopamine (PDA) coated in the surface of energetic materials is efficient in properties improving for its high adhesion. However, the key problem is the slow polymerization process of dopamine that often takes about 10 hours up to a few days, which hinder the development and limit its large‐scale application in most areas. Herein, an oxidant‐speed up method was proved to accelerate dopamine polymerization and it was successfully coated in the surface of 2, 6‐diamino‐3, 5‐dinitropyrazine‐1‐oxide (ANPZO) crystals. The SEM images, XRD patterns, FT‐IR spectra, and Raman spectrum indicated that the morphological and structural features had no change in the process of coating and the XPS spectrum indicated that the PDA has successfully occurred on the crystal surface. In addition, the ANPZO crystals coated with PDA had more excellent thermal stability and mechanical properties than uncoated ANPZO, with the unchanged sensitivity as a high‐energy insensitive explosive. This work opened up a new idea in accelerating self‐assembly and PDA modifications for surface by oxidant‐speed up method, which will promote the progess of insensitive high explosives and meet its application demand. Abstract :